Recent Advances in Nanocarrier-mediated Combination Drug Therapy for Tackling Solid-resistant Tumors - Rafiya, Km; Awasthi, Sakshi; Qureshi, Saba Asif; Hasan, Nazeer; Ahmad, Farhan Jalees (Current Drug Delivery, 2025)
Cancer is a group of dynamic diseases characterized by uncontrollable growth and spread of cells. The heterogenic nature of cancer hinders the abolishment of cancer resulting in a narrow therapeutic index, the capacity of drug efflux, multidrug resistance, and unacceptable side effects. The major challenge in the treatment of malignancies is multidrug resistance (MDR). A novel platform, nanoscale delivery system, concluding desirable applications for the treatment of cancer with targeted and controlled release of drugs, reducing the number of side effects and systemic toxicity. Recent studies emphasize that combining 2 or more nanocarrier-mediated therapies may produce complementary therapeutic effects, perhaps resulting in improved outcomes of cancer current therapies like deterioration of drug resistance. Therefore, in this article, we scrutinize the recent advancement addressing combination therapy by combining nanoparticles with anticancer drugs. It briefly concludes a thorough overview of cancer, tumor or solid resistant tumors, the mechanism of resistant tumors, current therapies for the treatment of solid tumors, and their challenges. It also covers various types of nanoparticles used in cancer treatment, the usage of nanocarriers in resistant tumors, and nanocarrier-based combinatorial therapy for the treatment of resistant tumors as well as its benefits. However, this approach still needs to be improved for clinical applications.
Keywords: drug delivery system